Living in a college environment or staying off-campus? A qualitative assessment of students’ life at the Mawar College, Universiti Teknologi MARA (UiTM) / Ahmad Naqiyuddin Bakar, Norwahidah Abd Wahid and Amizar Mohd Amin - Bakar, Ahmad Naqiyuddin; Abd Wahid, Norwahidah; Mohd Amin, Amizar (Universiti Teknologi MARA, Shah Alam, 2016)
The article examines the students’ life at the Mawar College, Universiti Teknologi MARA (UiTM) and their intention to stay off-campus. Students’ profile exhibits differences in composition by family background, ethnicity, academic programme, level of studies and secondary schooling. In‐depth interviews with college officials, college representatives committee and observations of general college environment provide insights into the way in which students adapt themselves into college life. Results illustrate that adaptation of Mawar students, in the light of their previous education (schooling) (and earlier stay in College during the school time), support the gross observation of a stronger chance of their adjustment into college life. The potential to thrive by Mawar students appears to be related to their secondary schooling as well as their previous level of studies that contribute to the familiarity with campus environment. Little direct evidence is found, however, to explain variations of adjusting to the college life and staying off-campus by family background, ethnicity, and academic programme. A tentative suggestion is proposed however that marginal composition of students based on their academic programme might account for these variation rate of thriving in college environment. It is recommended that future research should use different methods, such as experiments or detailed observations, to gain a better viewpoint on students’ level of adaptation in a college environment. The article concludes by considering implications for designing the practical programmes at college level thereby maximising their potential to excel.